ANALISIS KONDISI BAWAH PERMUKAAN DAN RISIKO BENCANA TANAH LONGSOR UNTUK ARAHAN PENATAAN KAWASAN DI DESA TENGKLIK KECAMATAN TAWANGMANGU KABUPATEN KARANGANYAR JAWA TENGAH - Naryanto, Heru Sri (Badan Pengkajian dan Penerapan Teknologi, 2011)
Karanganyar District is a hilly area with steep slopes, rock constituent of young volcanic deposits of Lawu Volcano products, thick soil and relatively high rainfall, so it is potential for large landslides in this region. The landuse in the Karanganyar District including the Tengklik Village is generally dominated by rice fields, seasonal gardens and settlements. Plantation made up in areas with steep topography has great influence on erosion and landslides. Similarly, many settlements are built on a slope so that the area is very vulnerable to the threat of landslides. In the rainy season landslides are common. The potential hazard of landslidesoccurred in 14 sub districts in Karanganyar District. Large landslides have occurred in Karanganyar on December 26, 2007 which claimed the lives of 62 people, with the greatest victims were in the Ledoksari Village, Tawangmangu. The Tengklik Village has already experienced creep type landslides, which have destroyed settlements, roads, seasonalgardens and all existing infrastructure in the area. In order to do the proper handling and anticipation of a catastrophic landslide, a variety of technological applications landslides using geographic information system (GIS) was then carried out, to detect the configuration of 2D geoelectrical subsurface prone areas for landslide risk study and regional planning.